Economic development: theory, history, policy - Meier, Gerald M.; Baldwin, Robert E. (New York: Wiley, 1957)
This book examines the problems of accelerating development in less developed countries and maintaining development in developed countries. The book includes topics like: what is economic development; classical analysis of authorities like Adam Smith and Ricardo; Marxian analysis; Neo-classical analysis; post-Keynesian analysis; Historical outlines of economic development; accelerating development in poor countries.
Includes bibliographies.
lje 03/09/2018
Loans
Keywords: Economic development